Central Obesity and Type 2 Diabetes Mellitus Among Adults Aged 19—64 Years in DKI Jakarta: A Cross-Sectional Study - Talitha Dwi Maharani; Ulya Qoulan Karima; Chahya Kharin Herbawani; Terry Y.R. Pristya (Jurnal Ilmiah Kesehatan Masyarakat : Media Komunikasi Komunitas Kesehatan Masyarakat, 2026)
Background: Type 2 diabetes mellitus (T2DM) is a metabolic disorder characterised by elevated blood sugar levels due to impaired insulin secretion in the body. Central obesity (CO) has been associated with insulin resistance and may contribute to the occurrence of T2DM. This study aimed to analyse the association between CO and T2DM among adults aged 19–64 years in DKI Jakarta. Methods: A cross-sectional study was conducted using secondary data from the Indonesian Health Survey (IHS) 2023. A total of 7,432 adults aged 19–64 years residing in DKI Jakarta were included. Multivariable logistic regression was performed to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for the association between CO and T2DM. Results: The prevalence of T2DM was 1.8%. CO was significantly associated with T2DM (p=0.001). Adults with CO had higher odds of T2DM compared with those without CO (adjusted POR=7.15; 95% CI: 2.19–23.35). Physical inactivity (adjusted POR=5.26; 95% CI: 1.64–16.90), heavy smoking (adjusted POR=2.34; 95% CI: 1.01–5.42), and hypertension (adjusted POR=3.79; 95% CI: 2.58–5.57) were also independently associated with T2DM. A statistically significant interaction between CO and physical activity was identified. Conclusions: Central obesity was strongly associated with T2DM among adults aged 19–64 years in DKI Jakarta. These findings underscore the importance of obesity and lifestyle-related factors in the epidemiology of T2DM. It is recommended for individuals to adopt a healthy lifestyle and undergo regular health checks to facilitate the early detection of CO and other health conditions.